GATA1 Activity Governed by Configurations of cis-Acting Elements - Hasegawa, Atsushi; Shimizu, Ritsuko (Frontiers in Oncology, 2017)
The transcription factor GATA1 regulates the expression of essential erythroid and megakaryocytic differentiation genes through binding to the DNA consensus sequence WGATAR. The GATA1 protein has four functional domains, including two centrally located zinc-finger domains and two transactivation domains at the N- and C-termini. These functional domains play characteristic roles in the elaborate regulation of diversified GATA1 target genes, each of which exhibits a unique expression profile. Three types of GATA1-related hematological malignancies have been reported. One is a structural mutation in the GATA1 gene, resulting in production of a short form of GATA1 that lacks the N-terminal transactivation domain and is found in Down syndrome-related acute megakaryocytic leukemias. The other two are cis-acting regulatory mutations affecting expression of the Gata1 gene, which are described as causes of acute erythroblastic leukemias and myelofibrosis in mice. Therefore, imbalanced gene regulation caused by qualitative and quantitative changes in GATA1 is thought to be involved in specific hematological disease pathogenesis. In the present review, we discuss recent advances in understanding the mechanisms of differential transcriptional regulation by GATA1 during erythroid differentiation, with special reference to the binding kinetics of GATA1 at conformation-specific binding sites.